The Librarian and Reference Queries: A Systematic Approach - Gerald Jahoda 1925-; Judith Schiek Robinson 1947- (USA Academic Press, 1980)
Abstract: A model framework for decision-making in the process of answering reference questions is presented for use by librarians and instructors of library science. Each step in the reference process is examined, and exercises for practicing each step are given with the goal of preparing students to search for answers to reference queries in a systematic fashion. These steps include isolating the essential message of each query by selection of message descriptors. Categories of answer-providing reference tools are described, with hints for selecting specific headings to search. These include the card catalog, encyclopedias, guides to the literature, indexes, bibliographies, abstracts and directories. Techniques for query negotiation are given. The characteristics of bibliographic data bases and guidelines for on-line searching are discussed. Emphasis is put on the kinds of information found in different reference materials
Keywords: General Knowledge (3GdeYGQa GdYGeIs; General; Reference services (Libraries)